Prolonged survival of a patient with aortogastric fistula treated with combined surgery and endovascular stent placement: A case report. (April 2021) - Sumiya, Ryusuke; Yamada, Kazuhiko; Nohara, Kyoko; Enomoto, Naoki; Igari, Toru; Kokudo, Norihiro
Highlights: The treatment for aortogastric tube fistula with active infection is challenging. The patient developed aortogastric tube fistula after lower esophagectomy. Repetitive surgical approach allowed hemodynamic and infection control. There had been no recurrence of esophageal cancer and stent issues for 22 years. Abstract: Introduction: Aortogastric tube fistula is a rare and fatal complication of esophagectomy. The treatment for aortogastric tube fistula with active infection is challenging, wherein a contamination around the fistula can cause a high risk of aneurysm and recurrence of bleeding, even if large amount of bleeding is controlled immediately. Presentation of case: We present a case of a 54-year-old male patient who underwent lower esophagectomy for esophageal squamous cell carcinoma 22 years ago. He developed aortogastric tube fistula on postoperative day 46. The patient underwent two surgeries and stenting for aortogastric tube fistula and pseudoaneurysm between days 46 and 120 following the first surgery, and digestive reconstruction was performed 6 months after the first surgery. Computed tomography and esophagogastroduodenoscopy were performed periodically, and the postoperative course was uneventful for 22 years. However, the patient died from pneumonia at the age of 76 years. Autopsy findings revealed no recurrence of esophageal cancer, anastomotic complications, or stent issues. The fistula between the aorta and gastric tube was closed with a stent and connective tissue. Intrathoracic findings revealed that the cause of death was severe bilateral pneumonia. Discussion: Immediate hemodynamics stabilization and interval infection control enabled successful disease management. Conclusion: Tenting for aneurysm was performed under aseptic conditions, and the patient did not experience recurrence of esophageal cancer and stent issues, which contributed to the long-term survival of 22 years.